INNOVATION MANAGEMENT: TYPES, MANAGEMENT AND INNOVATION PERFORMANCE IN ALBANIA - Feimi, Dorjana; Kume, Vasilika (European Scientific Journal, ESJ, 2014)
Purpose – The purpose of this study is to investigate the different types of innovation that are dominate in companies in the Albania services sector (telecommunication and bank), the praxis associated with the inquiry of innovation and their relationship with company performance. Design/methodology/approach – The study is a conceptual one with detailed review of literature and descriptive research design. This study collected quantitative data from 16 banks and 89 companies of telecommunications in Albania using a self-administered questionnaire. The questionnaires have been answered mainly by owners of businesses and sometimes by accountants of businesses. The article proceeds as follows. Section two and three offers the objectives of the study and the rational of the study. Next section offers the literature review. Also we try to give the performance of innovation in our country. Section six offers analysis and discussion of results in the context of other contributions to the topic. The final section presents a summary and tentative conclusion. Findings: Main findings show that more than 60% applies process and product innovation. Yet, these days Albania represents a deficit in innovation, with a poor performance, which becomes a handicap for the competitiveness of its enterprises. It ranks 123 out of 144 in Global Competitiveness Report 2012-2013. Research limitations: The period of the study is for six months from June 2013 to January 2014. The firm reports if it has introduced at least one innovation in the period from 2010 to 2012.